2010
DOI: 10.1007/s11999-010-1388-3
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Foreign-body Reaction to Absorbable Implants in Metacarpal Fracture Treatment

Abstract: Background First-generation bioabsorbable implants have been associated with a high complication rate attributable to weak mechanical properties and rapid degradation. This has led to the development of stronger devices with improved durability. However, the modern implants have raised concerns about potential late-occurring adverse reactions. Questions/purposes This retrospective study addressed the following questions: Can absorbable implants consisting of trimethylene carbonate, L-lactide, and D,L-lactide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 31 publications
0
75
1
Order By: Relevance
“…3,6,8 Foreign body reaction was associated with third-generation implants too. 22 In our study, we used a second-generation screw (RFS screw) for fixation of the coracoid process during the Latarjet procedure. This screw is composed of a copolymer of L-lactic/co-glycolic acid (PLGA 85L/15G), which is reported by the manufacturer to be fully resorbed within 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…3,6,8 Foreign body reaction was associated with third-generation implants too. 22 In our study, we used a second-generation screw (RFS screw) for fixation of the coracoid process during the Latarjet procedure. This screw is composed of a copolymer of L-lactic/co-glycolic acid (PLGA 85L/15G), which is reported by the manufacturer to be fully resorbed within 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…All fractures united and there were no reported complications with a minimum of 6-month follow-up [39]. Prospective, randomized controlled trials of absorbable plates are lacking, however, and delayed foreign body reactions have been described up to 2 years after fracture fixation [17]. Bioabsorbable plates are also more expensive, and one cost-benefit analysis found that a hardware removal of at least 19 % would be required to break even as compared to use of metal plates [6].…”
Section: Operative Treatmentmentioning
confidence: 99%
“…The incidence of foreign body reactions in our study was 4.8% (9/186), which is slightly lower than that of 6.1% reported in the study by Böstman (26). Although foreign body reactions occurred and fluid accumulated topically, the fracture healing was uneventful (27). AIs had no specific inhibitory and stimulatory effects on bone compared with metal materials (28).…”
Section: Discussionmentioning
confidence: 99%